Aplikasi Game Edukasi Tajwid Berbasis Android - Yusmiarti, Kusnita; Triawan, Medi (STMIK Bina Nusantara Jaya Lubuk Linggau, 2023)
An Android-based Tajweed Educational Game Application for Madrasah Diniyah takmiliyah, Pagar Alam City, still uses the manual method, namely the conventional method in the form of books and blackboards. This makes it sometimes difficult for children to remember and understand the material presented by the students. By doing an analysis of the existing problems, namely the absence of interesting and interactive learning media at Madrasah Diniyah takmiliyah Insan Madani, an Android-based Tajweed Educational Game Application was created. The application was built using Construct 2, and using the Development Life Cycle (GDLC) method. This application is also equipped with audio, visual and pictures of numbers, letters, with the concept of learning while playing which aims to help children more easily remember and understand Tajwid and make it easier for students to learn. students to provide the material to be delivered Keywords: Tajwid educational game application, Android, Construct 2, GDLC